Analisis Soal-soal Buku Ajar Matematika Kelas VII Ditinjau dari Taksonomi Bloom Revisi - Prasetya, Irfan Yuni, Drs. Ariyanto, M.Pd (2017)
This study aimed to analyze the questios in the textbook of mathematics for the seven-grade level of Junior High School revised edition 2016 of curriculum 2013 which reviewed from cognitive aspect based on Bloom's Taxonomy of revisions. Cognitive aspect based on Bloom's Taxonomy of revisions consists of dimensions of knowledge and dimensions of cognitive process. Dimensions of knowledge include factual, conceptual, procedural, metacognitive, and dimensions of cognitive process include remembering, understanding, applying, analyzing, evaluating, creating. In this research will be gradually analyzed the cognitive level on such questions based on the dimensions of knowledge and cognitive processes, then entered into the Taxonomy Table.The results of this study indicate that the overall questions in textbook semester 1 and 2 amounted to 965 grains, after classification there is 5.28% C1-factual level; 3.32% C2-factual level; 18.34% C2-conceptual level; 10.16% C3-conceptual level; 32.12% C3-procedural level; 7.88% C4 level-conceptual;15.85% C4 level-procedural;3.01% C5-conceptual level; 2.28% C5-procedural level; 1.46% C6-conceptual level; and there are 0.31% wrong or damaged questions.The conclusion of this research is that the questions in the textbook are quite varied, but for the division of each aspect is less evenly and still low the number of high-order of thinking questions, so that the book needs to be revised in a sustainably to get a better book and can improve the quality of education in Indonesia.